Integration of Maqaṣid al-Shari'ah in the Criminal Law Reform to Achieve Justice and Human Dignity - brahim, Zumiyati Sanu; Karimullah, Suud Sarim; Assaad, Andi Istiqlal; Septiani, Rina; Okur, Huseyin (Jurnal Hukum Islam, 2025)
In this postmodern era, when the boundaries between local and global are increasingly blurred, efforts to build a contextual, ethical, and responsive criminal justice system have become an urgent necessity. This study aims to propose a model of criminal law reform based on maqaṣid al-shari'ah that is more humane and just, emphasizing not only the imposition of sanctions or punishments but also the rehabilitation and restoration of offenders. This study is normative-juridical, employing a doctrinal analysis approach and reinforced by various relevant legal theories to provide a philosophical foundation for evaluating the application of maqaṣid al-shari'ah in contemporary criminal law needs. The results state that the integration of maqaṣid al-shari'ah in criminal law reform in Muslim-majority countries, including Indonesia, should not be viewed merely as a symbolic moderation between religious law and human rights, but as a transformative project that requires epistemological courage to overhaul the classical view of legal authority and the meaning of justice. Amidst the wave of globalization that challenges the supremacy of religious law and demands stronger protection of human dignity, maqaṣid is present not merely as passive theological values, but as active principles that require that law protect life, reason, freedom, and social welfare in concrete and measurable ways. The path toward integrating maqasid-based criminal law principles into the modern criminal legal systems of majority-Muslim countries is not a short-term project, as it requires a paradigm shift from a textualist approach to a contextual approach, from legalism to humanism, and from conservatism to intellectual courage.